Coaching competency and satisfaction with the coach: A multi-level structural equation model - Myers, N. D.; Beauchamp, M. R.; Chase, M. A. (Journal of Sports Sciences, 2011)
The purpose of this initial predictive validity study was to determine the ability of measures derived from the Athletes' Perceptions of Coaching Competency Scale II - High School Teams (APCCS II-HST) to predict satisfaction with the head coach. Specification of the statistical model was informed by the mediational model of coach-athlete interactions. The technical quality of the satisfaction measure was evaluated before testing the predictive validity of the coaching competency measures. Data were collected from athletes of seven sports. Athlete observations (N = 748) were clustered within teams (G = 74). Multi-group confirmatory factor analyses (CFA) provided evidence for factorial invariance of a reduced version of the satisfaction measure by athlete gender. Multi-level CFA provided evidence of model-data consistency for a reduced version of the satisfaction measure. Multi-level structural equation modelling provided evidence for the ability of latent coaching competency to positively predict latent satisfaction at both the athlete level (technique competency and motivation competency) and the team level (coaching competency) and for close model-data fit. Implications of this study include: that the APCCS II-HST should be viewed as a replacement for the Coaching Competency Scale when the intended population is appropriate; a preliminary multi-level measurement model for satisfaction with one's coach that should be considered as a potential starting point in subsequent studies; and empirical support for a key relationship proposed in the mediational model of coach-athlete interactions.